Structural evolution after oxidative pretreatment and CO oxidation of Au nanoclusters with different ligand shell composition: a view on the Au core. Issue 5 (19th January 2023) - Truttmann, Vera; Schrenk, Florian; Marini, Carlo; Palma, Mireia; Sanchez-Sanchez, Maricruz; Rameshan, Christoph; Agostini, Giovanni; Barrabés, Noelia
Abstract : The structural dynamics of supported monolayer protected Au nanoclusters after pretreatment and catalytic CO oxidation have been probed by XAS and XPS. Abstract : The reactivity of supported monolayer protected Au nanoclusters is directly affected by their structural dynamics under pretreatment and reaction conditions. The effect of different types of ligands of Au clusters supported on CeO2 on their core structure evolution, under oxidative pretreatment and CO oxidation reaction, was investigated. X-ray absorption and X-ray photoelectron spectroscopy studies revealed that the clusters evolve to a similar core structure above 250 °C in all the cases, indicating the active role of the ligand–support interaction in the reaction.